(untitled) (Revista Nacional de Odontología, 2013)
An impacted tooth organ is one whose eruption is obstructed by a physical barrier, which can be bone, soft tissue or an associated pathology. Establishing an appropriate treatment plan in such cases usually involves holding an inter-consultation and providing interdisciplinary management. The report presents a 17-year-old female patient who came for an appointment because of the permanence of a deciduous tooth in the anterior superior sector of her mouth. Clinical examination revealed the persistence of dental organ 52; radiography showed a radiopaque lesion with a radiolucent edge compatible with odontoma. The treatment plan consisted of the hygienic phase, extraction of deciduous dental organ 52, enucleation of the odontoma and orthodontic traction of the impacted tooth to align it with the occlusal plane. In a control visit, mucogingival surgery was proposed to correct aesthetic defects following orthodontic traction. The aim in presenting this case is to describe an interdisciplinary approach to a retained lateral in the maxilla.